Pengaruh Latihan Crossover Dribble dan Behind the Back Dribble terhadap Teknik Dribbling pada Atlet Putra Bola Basket Usia 13-14 Klub Singa Muda - Jimmy Daniel; Gede Eka Budi Darmawan; Syarif Hidayat (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to investigate the effects of crossover dribble and behind-the-back dribble training on the dribbling techniques of male basketball players from the Singa Muda club aged 13 to 14 years. A quantitative approach was used, employing a two-group quasi-experimental pre-test and post-test design with 50 athletes. The athletes were divided into two groups: a crossover dribble training group and a behind-the-back dribble training group, each consisting of 25 athletes. Using SPSS, paired and independent t-tests were employed to analyze the data at a significance level of α = 0.05. The study findings indicate that improvements in dribbling technique among male athletes aged 13 to 14 years at the Singa Muda Club were significantly influenced by crossover dribble and behind-the-back dribble training, and there were significant differences between the two types of dribble training. These results indicate that players’ motor coordination, ball control, and dribbling agility can be enhanced through technical instruction that is precise, well-planned, and repetitive. For adolescent basketball players, crossover dribble training may be a more efficient way to improve dribbling technique.